Cell culture and Drosophila model systems define three classes of anaplastic lymphoma kinase mutations in neuroblastoma - Damini Chand (Disease Models & Mechanisms, 2013)
SUMMARY Neuroblastoma is a childhood extracranial solid tumour that is associated with a number of genetic changes. Included in these genetic alterations are mutations in the kinase domain of the anaplastic lymphoma kinase (ALK) receptor tyrosine kinase (RTK), which have been found in both somatic and familial neuroblastoma. In order to treat patients accordingly requires characterisation of these mutations in terms of their response to ALK tyrosine kinase inhibitors (TKIs). Here, we report the identification and characterisation of two novel neuroblastoma ALK mutations (A1099T and R1464STOP), which we have investigated together with several previously reported but uncharacterised ALK mutations (T1087I, D1091N, T1151M, M1166R, F1174I and A1234T). In order to understand the potential role of these ALK mutations in neuroblastoma progression, we have employed cell culture-based systems together with the model organism Drosophila as a readout for ligand-independent activity. Mutation of ALK at position 1174 (F1174I) generates a gain-of-function receptor capable of activating intracellular targets such as ERK (extracellular signal regulated kinase) and STAT3 (signal transducer and activator of transcription 3) in a ligand-independent manner. Analysis of these previously uncharacterised ALK mutants and comparison with ALKF1174 mutants suggests that ALK mutations observed in neuroblastoma fall into three classes. These classes are: (i) gain-of-function ligand-independent mutations such as ALKF1174l, (ii) kinase-dead ALK mutants, e.g. ALKI1250T (Schönherr et al., 2011a) and (iii) ALK mutations that are ligand-dependent in nature. Irrespective of the nature of the observed ALK mutants, in every case the activity of the mutant ALK receptors could be abrogated by the ALK inhibitor crizotinib (Xalkori/PF-02341066), albeit with differing levels of sensitivity.